Association between abnormal electrocardiogram and less complex heart rate variability estimated by the correlation dimension - Lerma, C.; Reyna, M A.; Carvajal, R. (Revista Mexicana de Ingenieria Biomedica, 2015)
Objective: To compare the correlation dimension (CD) of heart rate variability (HRV) in adults with and without abnormal electrocardiogram (ECG). Methods: A 24-hr Holter and a standard ECG were recorded from 100 university workers. After exclusion of 10 recordings with more than 5% of false RR intervals, a total of 90 subjects (age 46.2 ± 8.7 years old, 45 were women) were included in the study. Two cardiologists classified 29 standard ECG as abnormal. CD was calculated from HRV time-series of 10,000 beats in the morning (from 11am), afternoon (from 5pm) and night (from 2am). Demographical characteristics were compared by ANOVA (considering ECG diagnosis and sex as independent factors) or by Fisher’s exact test. Mean CD values were compared by analysis of variance considering as independent factors the ECG diagnosis, sex and time of day. Results: All demographical characteristics were similar except for a higher proportion of males with abnormal ECG (69%) than with normal ECG (41%). CD was not different with respect to the time of day, but it was higher in subjects with normal ECG (10.86 ± 2.41) than those with abnormal ECG (10.20 ± 2.48), and it was also higher in females than males: 11.04 ± 2.14 versus 10.63 ± 2.71 (normal ECG group), 10.84 ± 2.41 versus 9.92 ± 2.44 (abnormal ECG group). Conclusion: The finding of abnormal ECG is associated with HRV decreased complexity in adults.